Beneficial Effect of Bidens pilosa on Body Weight Gain, Food Conversion Ratio, Gut Bacteria and Coccidiosis in Chickens - Chang, Cicero L. T.; Chung, Chih-Yao; Kuo, Chih-Horng; Kuo, Tien-Fen; Yang, Chu-Wen; Yang, Wen-Chin (PloS one, 2016)
In the interests of food safety and public health, plants and their compounds are now re-emerging as an alternative approach to treat gastrointestinal diseases in chickens. Here, we studied the impact of the edible medicinal plant, B. pilosa, on growth performance, gut bacteria and coccidiosis in chickens. First, we found that B. pilosa significantly elevated body weight gain and lowered feed conversion ratio in chickens. Next, we showed that B. pilosa reduced cecal damage as evidenced by increased hemorrhage, villus destruction and decreased villus-to-crypt ratio in chicken ceca. We also performed pyrosequencing of the PCR ampilcons based on the 16S rRNA genes of gut bacteria in chickens. Metagenomic analysis indicated that the chicken gut bacteria belonged to 6 phyla, 6 classes, 6 orders, 9 families, and 8 genera. More importantly, we found that B. pilosa affected the composition of bacteria. This change in bacteria composition was correlated with body weight gain, feed conversion ratio and gut pathology in chickens. Collectively, this work suggests that B. pilosa has beneficial effects on growth performance and protozoan infection in chickens probably via modulation of gut bacteria.